Manajemen tata ruang perpustakaan pesantren madani Alauddin Pao-Pao Makassar - Muhammad Azwar; Agung Nugraha Rusli (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2016)
This paper discusses the library building design at school library Madani Alauddin Pao-pao. Thelibrary building design is one of the aspect of library development that has the prominent role incarrying out and successing the library functions. A good library design has significant impactto increase users’ interest to visit and use the library services due to the the comfort of the studyenvironment. The purpose of the research ís to examine the library building design of PesantrenMadani Alauddin Pao-pao and to know whether the school library of Pesantren Madani Pao-pao hasfulfilled the National standard of school library (SNP 009:2011).